Saint Augustine and the romantic aesthetics - García Vázquez, Milagros (Pensamiento. Revista de Investigación e Información Filosófica, 2021)
This article proposes possible connections between the Augustinian mysticism and the aesthetic thought of St. Augustine, with the main basis of German Romanticism represented by three authors, Wilhelm Heinrich Wackenroder and his text Confessions of a monk in love with art, Caspar David Friedrich and his painting Monk facing the sea, and Novalis and his lyrical, narrative and essays. In this way, it is sought to leave open another possible way of approaching the romantic movement and knowledge of its ideals that could complete the perspectives from which the lives and works of these authors have been already studied. Similarly, it could be assessed the modernity of Augustinian thought and its validity centuries after its time, not only in the theological aspect, but also in the literary and aesthetic.
Keywords: Saint Augustine; Wackenroder; C. D. Friedrich; Novalis; Romanticism; aesthetics